2015
DOI: 10.3945/an.115.008870
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perception of Genetically Modified Organisms and Sources of Information

Abstract: Genetically modified organisms (GMOs) have been available for commercial purchase since the 1990s, allowing producers to increase crop yields through bioengineering that creates herbicide-resistant and insect-resistant varieties. However, consumer knowledge about GMOs has not increased at the same rate as the adoption of GMO crops. Consumers worldwide are displaying limited understanding, misconceptions, and even unfamiliarity with GMO food products. Many consumers report that they receive information about GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
153
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(169 citation statements)
references
References 15 publications
9
153
3
4
Order By: Relevance
“…Although existing studies have suggested that people's scientific knowledge impacts their attitudes towards GM food [e.g. Wunderlich and Gatto, 2015], people's scientific knowledge does not necessarily reflect their perception and acceptance of the technology. In the process of making decisions about controversial food technologies, researchers note that members of the public can make decisions without ample relevant scientific knowledge.…”
Section: Scientific Consensus On Public Perception and Decisionmentioning
confidence: 99%
“…Although existing studies have suggested that people's scientific knowledge impacts their attitudes towards GM food [e.g. Wunderlich and Gatto, 2015], people's scientific knowledge does not necessarily reflect their perception and acceptance of the technology. In the process of making decisions about controversial food technologies, researchers note that members of the public can make decisions without ample relevant scientific knowledge.…”
Section: Scientific Consensus On Public Perception and Decisionmentioning
confidence: 99%
“…On the other hand, the item that had the worst correlation with almost all other items was number 10, associated to the consumption of genetically modified foods (GM foods). GM foods are still a controversial subject, due to lack of knowledge, misconceptions and even a lack of familiarity with GM food products by worldwide consumers [26].…”
Section: Itemsmentioning
confidence: 99%
“…Similarly, when a product is labeled “organic,” consumers perceive it to be nutritious (Andrews et al, ; Chandon & Wansink, ; Roe et al, ) and low‐calorie (Lee et al, ). Consumers who are familiar with genetically modified organism (GMO) prefer non‐GMO food (Wunderlich & Gatto, ), and consumers who prefer non‐GMO goods have higher likelihood of purchasing them (Vecchione, Feldman, & Wunderlich, ). In Haroldson and Yen's () pilot study, the majority of participants believed non‐GMO foods were somewhat or very healthy in general (Haroldson & Yen, ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%